Gourmetization and gentrification: Food landscapes from the city to the countryside - Di Virgilio, María Mercedes (2024)
This article contributes to developing and consolidating research on the connections between food and gentrification while highlighting the effects of these processes in areas beyond urban life. To achieve this, we draw on the concept of value chains connecting gentrified neighborhoods to rural agricultural communities. In this chain, processes of valorization and devaluation are generated, which unevenly affect the actors involved in the production and consumption of food. The paper focuses on the conflicts and contestations along the value chain of gentrification, putting interdisciplinary contributions into dialogue while presenting four cases from secondary sources. These cases are illustrative of how these processes operate at different levels, territories, and scales: signature coffee, as a symbol of distinction in gentrified neighborhoods; the avocado from its gastronomic manifestation as avocado toast; wine, from the touristification of its production to valorization strategies in urban consumption; and quinoa, from the patenting of new varieties to the development of markets that exclude large sectors of the population. The boom in the circulation of these foods has the effect of capital accumulation by dispossession in both rural and urban areas and in both production and consumption processes.